STRATEGI PEMASARAN ISLAMI YANG MENGINTEGRASIKAN ETIKA DAN TEKNOLOGI DALAM MENDUKUNG KEBERLANJUTAN BISNIS - Enceng, Enceng Iip Syaripudin; Deni, Deni Kon Kon Furkony; Gini, Gini Gaussian; Ujang, Ujang Burhanudin; Kiki, Kiki Rofi'ah Alawiyah; Saep, Saep Saepudin (LEMBAGA PENELITIAN DAN PENGABDIAN PADA MASYARAKAT, 2025)
This study examines Islamic marketing strategies that integrate ethical principles and technology tosupport the sustainability of Islamic businesses in Garut Regency. The main focus of the research is toanalyze the challenges faced by Islamic business actors in the area, such as the consistent application of Islamic ethics, the underutilization of technology, and competition with conventional businesses.Additionally, factors such as the lack of market education and digital infrastructure pose significantbarriers to enhancing the competitiveness of Islamic businesses in Garut Regency. This research uses aqualitative method with a case study approach, involving in-depth interviews with Islamic businessactors in Garut Regency, observations of marketing practices, and document analysis. The findingsindicate that collaboration between Islamic values and technological innovation can create moreeffective marketing strategies, expand market reach, and build consumer trust. The study providespractical recommendations for Islamic business actors in Garut Regency to enhance theircompetitiveness in facing global market dynamics while maintaining Islamic principles